2007
DOI: 10.5132/jbse.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genotoxicity Induced by Atmospheric Pollution Using the Land Mollusk Cantareus aspersus (Müller, 1774) as Biomonitor and the Comet Assay as Biomarker

Abstract: The objective of this work was to investigate the viability of using the land mollusk Cantareus aspersus (Müller, 1774) as biomonitor and the Comet Assay as biomarker, exposing organisms to atmospheric pollutants. Organisms were exposed to air at the Ulbra University campus climatic control station (Canoas, RS) for 7, 15 and 30 days, in the winter/2004 and in the summer/2005. Our control group, not exposed, was kept in the laboratory, under controlled conditions. Lung cells and hemolymph cells were evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Recently, some studies have demonstrated biological effects of air pollution in urban regions. Silva et al (2007) found genotoxicity in mollusks Cantareus asperses, from Southern Brazil (Canoas, Rio Grande do Sul State), and related the effects to atmospheric contamination. Also, in São Paulo, epiphytic lichens were used as a biological index for chemical quantification of pollutants concentrated by the Canoparmelia texana lichenized fungi (Fuga et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have demonstrated biological effects of air pollution in urban regions. Silva et al (2007) found genotoxicity in mollusks Cantareus asperses, from Southern Brazil (Canoas, Rio Grande do Sul State), and related the effects to atmospheric contamination. Also, in São Paulo, epiphytic lichens were used as a biological index for chemical quantification of pollutants concentrated by the Canoparmelia texana lichenized fungi (Fuga et al 2008).…”
Section: Introductionmentioning
confidence: 99%